2021
DOI: 10.1021/acs.langmuir.1c01339
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Friction Dynamics of Oil-in-Water and Water-in-Oil Emulsions on Hydrogel Surfaces

Abstract: In this study, the friction properties of emulsions in an oral environment were investigated to understand the food-texture recognition mechanisms occurring on biological surfaces. Numerous publications have suggested that the friction phenomena depend on friction conditions, such as the surface characteristics, as well as the shape and movement of contact probes. Traditional friction evaluation systems are unsuitable for mimicking the oral environment. Thus, in this study, the friction forces between two frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We observed that the δ was affected by various factors such as the hardness and thickness of the material and viscosity of the fluid. 16,18,19 Conversely, in the case of surfactant aqueous solution 2, static friction and a sharp increase in friction force were observed (Figure 2b). In the outward direction, no static friction was observed, and the friction force increased to 0.25 N during the kinetic friction process.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We observed that the δ was affected by various factors such as the hardness and thickness of the material and viscosity of the fluid. 16,18,19 Conversely, in the case of surfactant aqueous solution 2, static friction and a sharp increase in friction force were observed (Figure 2b). In the outward direction, no static friction was observed, and the friction force increased to 0.25 N during the kinetic friction process.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…The various dissipative modes of foam cause a decrease in the effective friction coefficient as sliding speed increases. It is possible that the viscous dissipation ,, and the dissipation related to surfactant diffusion affect the friction dynamics of foam because a thick lubricating film was formed between the plates. In addition, the dissipation related to wall slip of bubbles is one of the most important modes because a smooth acrylic plate was used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Key words: organogel, wax, friction, hardness, gelation Y. Nonomura, H. Ogura, H. Niino et al served 11) . In the friction of bubbles between acrylic plates, static friction does not occur, and a friction profile, in which the friction force increases according to velocity, is observed 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we developed a sinusoidal‐motion friction evaluation system that combines a sinusoidal‐motion friction evaluation device and fractal agar gel to mimic the physical characteristics of the wet, soft, hydrophilic, and rough tongue, buccal meatus and palate and the motion of the tongue with acceleration (Aita et al, 2017; Kikuchi et al, 2021; Kikuchi et al, 2022; Okawara et al, 2020). The elastic modulus of the fractal agar gel was 0.90 ± 0.06 × 10 6 Pa.…”
Section: Introductionmentioning
confidence: 99%